2020
DOI: 10.18176/resp.0003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed diabetes and optimal disease control of prisoners in Catalonia

Abstract: Determinar la prevalencia de diabetes diagnosticada (DD) y su control en presos de Cataluña. Material y métodos: Estudio transversal realizado en cuatro prisiones catalanas de hombres, entre abril y mayo de 2016. Se calculó la prevalencia de DD mediante un muestreo intencional, recogiéndose: a) datos de diabetes: tipo, valor de hemoglobina glucosilada (HbA1c) y tratamiento; b) comorbilidades; c) variables epidemiológicas y penitenciarias; d) conocimiento sobre hiperglucemia/hipoglucemia; y e) participación en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that many inmates sentenced to long incarceration periods gain weight, with obesity rates rising during incarceration [ 9 , 10 ]. Furthermore, obesity co-morbidities, such as diabetes, hypertension, and atherosclerosis are on the rise among inmates [ 11 , 12 , 13 , 14 ]. Underweight is also prevalent among inmates, mostly within developing countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that many inmates sentenced to long incarceration periods gain weight, with obesity rates rising during incarceration [ 9 , 10 ]. Furthermore, obesity co-morbidities, such as diabetes, hypertension, and atherosclerosis are on the rise among inmates [ 11 , 12 , 13 , 14 ]. Underweight is also prevalent among inmates, mostly within developing countries [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Psychiatric and digestive pathologies are the health problems that affect inmates most commonly [4]. An increased risk of diet-related diseases, e.g., overweight [5,6], obesity [5,6], diabetes [7][8][9], atherosclerosis [8,10], and arterial hypertension [4,8,10], is observed as well. The development of this type of disorder 2 of 14 is promoted by many other factors that are not directly related to physical inactivity or inadequate nutrition, e.g., primarily drug use, alcohol abuse, and smoking [11].…”
Section: Introductionmentioning
confidence: 99%